Tubulointerstitial expression and urinary excretion of connective tissue growth factor 3 months after renal transplantation predict interstitial fibrosis and tubular atrophy at 5 years in a retrospective cohort analysis. (9th May 2017) - Vanhove, Thomas; Kinashi, Hiroshi; Nguyen, Tri Q.; Metalidis, Christoph; Poesen, Koen; Naesens, Maarten; Lerut, Evelyne; Goldschmeding, Roel; Kuypers, Dirk R. J.
Summary: Connective tissue growth factor (CTGF) is an important mediator of renal allograft fibrosis, and urinary CTGF (CTGFu) levels correlate with the development of human allograft interstitial fibrosis. We evaluated the predictive value of CTGF protein expression in 160 kidney transplant recipients with paired protocol biopsies at 3 months and 5 years after transplantation. At month 3 and year 1, CTGFu was measured using ELISA, and biopsies were immunohistochemically stained for CTGF, with semiquantitative scoring of tubulointerstitial CTGF‐positive area (CTGFti). Predictors of interstitial fibrosis and tubular atrophy (IF/TA) severity at 5 years were donor age [OR 1.05 (1.02–1.08), P = 0.001], female donor [OR 0.40 (0.18–0.90), P = 0.026], induction therapy [OR 2.76 (1.10–6.89), P = 0.030], and CTGFti >10% at month 3 [OR 2.72 (1.20–6.15), P = 0.016]. In subgroups of patients with little histologic damage at 3 months [either ci score 0 ( n = 119), IF/TA score ≤1 ( n = 123), or absence of IF/TA, interstitial inflammation, and tubulitis ( n = 45)], consistent predictors of progression of chronic histologic damage by 5 years were donor age, induction therapy, CTGFti >10%, and CTGFu. These results suggest that, even in patients with favorable histology at 3 months, significant CTGF expression is often present which may predict accelerated accumulation of histologic damage.